Integrating Technology in English Language Teaching: A Study on Teachers' Digital Competencies - Lailatul Nurjanah; Bambang Yudi Cahyono; Nunung Suryati; Muhammad Idris Effendi (South Sulawesi Education Development (SSED), 2025)
The integration of technology in English Language Teaching (ELT) has emerged as a critical component of modern education, offering innovative tools to enhance learning experiences. This study aimed to explore the role of technology in ELT by examining teachers' digital competencies through a systematic review of 45 peer-reviewed articles published in the last decade. The research identifies key technologies utilized in ELT, such as online learning platforms, language learning applications, and interactive media, highlighting their advantages and challenges. The findings reveal significant variations in teachers' digital competencies, categorized as high, moderate, or low, with the majority requiring additional training to utilize digital tools effectively. Factors influencing technology adoption, including institutional support and teachers' attitudes, were also analyzed. However, the study underscores gaps in the literature, such as the absence of standardized frameworks for assessing digital competencies, limited research on the long-term impact of technology on learning outcomes, and insufficient attention to challenges faced by educators in developing countries. These findings emphasize the need for targeted professional development programs and robust infrastructure to bridge the digital competency gap. While advancing scientific knowledge on technology integration in ELT, the study acknowledges limitations related to geographic focus and reliance on secondary data. Future research should expand to diverse contexts and explore emerging technologies to enhance ELT practices globally.